Obstacles Facing Jordanians’ Turnout to Take the Covid-19 Vaccine: A Field Study in Irbid Governorate - Gazan, Abdullah; Abu Joudeh, Alaa Abdullah (Jordan Journal of Social Sciences, 2023)
The study aimed at exploring the social, health and source of information obstacles that prevented Jordanian people from taking the Corona vaccine. In addition, it aimed to identify the significant statistic differences for the obstacles that hinder citizens to take the Corona vaccine in terms of the community health awareness of Corona pandemic in different aspects. These obstacles are attributed to independent variables. To this end, the study designed a questionnaire to collect the data. The population of the study consisted of all the individuals who didn’t take the Corona vaccine in Irbid Governorate. The sample of the study, which was chosen by the intended method consisted of (247) individuals. The study relied on the descriptive analytical method and survey by sampling. The results of the study showed that the social and health obstacles came in medium and high degrees for the information sources axis. Moreover, there were no statistically significant differences for the independent variables (educational level, age, and marital status) for all study axes. It showed that there were differences between the arithmetic averages of the health axis according to the gender variable. The study recommended the need to highlight the role of the Ministry of Health in updating health information, and focusing on the importance of taking the vaccine on social networking sites and all media. The Ministry of Health should publish summaries of research and scientific studies related to vaccinations related to the Corona virus in a simple manner and in a language that is understandable to the readers.